Acoustic method for measuring the thickness of deposits on the inner wall of technological equipment - A. V. Suslov (Вестник Самарского университета: Естественнонаучная серия)
In the paper researches of the acoustic method for measuring the thickness of wax deposits on the inner wall of technological equipment are carried out. Experimental studies were conducted to study the combined effect of wall thickness, pipeline diameter and deposit thickness on the parameters of pipeline wall oscillation. Measurements of unknown deposit thicknesses have been carried out using a method based on the analysis of the parameters of pipeline wall oscillation. Experimental studies have been conducted to measure the irregular distribution of deposits. The obtained results allow, with good accuracy, to measure the thickness of wax deposits in technological equipment.